Clinical features of skin lesions in rabbit syphilis: A retrospective study of 63 cases (1999-2003) - Saito, K; Hasegawa, A (Journal of Veterinary Medical Science, 2004)
Skin lesions in rabbit syphilis are usually diagnostic, but it is occasionally difficult to differentiate these lesions from those of other skin diseases. Skin lesions in 63 cases of rabbit syphilis were analyzed for early and accurate diagnosis. Lesions were found most frequently around the nose (55 cases) followed by the genitalia (22), lips (20). eyelids (12), and anus (10). Sneezing was observed in 33% of cases with nasal lesions. In cases of maternally acquired infection, lesions could be initially found mainly on the face. Rabbits should be examined carefully not only for facial lesions, but also for lesions of the genitalia and anus, locations easily overlooked.